Perspectives on the adoption of black-soldier fly larvae for animal feed among livestock farmers in Sub-Saharan Africa - Nyamuhirwa, D.A.; Feleke, S.; Dontsop-Nguezet, P.; Sissoko, D.; Moussa, B.; Kouakou, A.G.; Zakari, S.; Abdoulaye, T.; Manyong, V. (Frontiers Media, 2025)
Introduction Black soldier fly larvae (BSFL) are increasingly promoted as cost-effective, and environmentally friendly source of protein in animal nutrition. However, there is limited information about farmers' adoption rates and the factors influencing their adoption decisions in Sub-Saharan Africa (SSA). This article assesses livestock farmers' actual and potential adoption rates of BSFL and determinants of their adoption decisions. Methods In this paper, we used the treatment effect framework approach on data collected from 1,885 fish, poultry, and pig smallholder farmers in five cities of four West and Central African countries, including Kinshasa and Bukavu in the Democratic Republic of Congo (DRC), Accra in Ghana, Bamako in Mali, and Niamey in Niger. Results and discussion The results show that about 20 percent of surveyed farmers are aware of BSFL as a protein source in animal feed, and the actual adoption rate of BSFL is four percent. However, the treatment effect analysis showed that the adoption rate could quadruple if all farmers were aware. This result suggests that successful awareness creation can boost the actual adoption of BSFL, which currently stands at four percent. The awareness creation should target educated livestock farmers with access to group membership, credit, extension services, and diversified income sources to influence their decisions to adopt BSFL as a source of protein in animal feed.